An Overview Of Ballistic Protective Clothing - Kumari, Pooja; Jajpura, Dr. Lalit; rani, Neetu (Innovative Research Thoughts, 2021)
Ballistic protective clothes are of great importance depending on the rapid developments in military area. Ballistic protection is one of the main functional characteristics of military textiles. Ballistic protective clothes protect the body by the absorption of the kinetic energy of the bullets and shrapnel. High strength fabrics are used in many industrial areas in connection with ballistic protection such as body armors, inner parts of plane or vehicles. The main parameters that affect the energy absorption are the fiber type, fabric construction, tightness and mass per unit area of the fabric and the number of the fabric layers used in the clothing material. The fibers used for this purpose should have high tenacity, high modulus and lower elasticity properties. Recently, para-aramid fibers are the most used fibers for ballistic protective clothes. Along with para-aramids, high molecular weight polyethylene fibers also are of importance commercially. Also, there are fibers for ballistic protection such as wholly aromatic polyester fibers, PBO and PIPD. Also, carbon nanotubes and spider silk fibers are thought to have great potential applications for ballistic-resistance materials with their remarkable properties. This article presents information about the ballistic protection mechanism of textile materials, the fibers used in those fabrics and the method, which is used to compare ballistic resistance of textile materials.